1991
DOI: 10.1002/ptr.2650050205
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory activity of Ipomoea pes‐caprae (L.) R. Br

Abstract: The antiinflammatory activity of an extract from the leaves of Ipomoea pes-caprae (L.) R. Br., used as a traditional remedy for different types of inflammation, was investigated using experimental models of acute inflammation. Topical application of the extract inhibited carrageenan-induced paw oedema and ear oedema induced in rats by arachidonic acid or ethyl phenylpropiolate. In uitro prostaglandin formation was inhibited by the extract in a concentration-dependent manner, with a potency equal to that of asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…By comparing the retention times, the selected ion current ( m/z = 51, 77, 107 and 135) profile, and the possible fragmentation mechanisms, we calculated that the structure of compound with retention time of 14.114 min was 4-hydroxy-3-methoxystyrene, which may be derived from decarboxylation of ferulic acid [15,16]. It has been reported to possess anti-inflammatory and anti-oxidative activity [17]. 4-Hydroxy-3-methoxystyrene levels increased with increasing boiling times and approximated the threshold value of 0.3 mg/L after 3 h [15].…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the retention times, the selected ion current ( m/z = 51, 77, 107 and 135) profile, and the possible fragmentation mechanisms, we calculated that the structure of compound with retention time of 14.114 min was 4-hydroxy-3-methoxystyrene, which may be derived from decarboxylation of ferulic acid [15,16]. It has been reported to possess anti-inflammatory and anti-oxidative activity [17]. 4-Hydroxy-3-methoxystyrene levels increased with increasing boiling times and approximated the threshold value of 0.3 mg/L after 3 h [15].…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary results of chemical investigation of Ipomoea pes caprae showed that the extract contains phenolic and terpenoid substances (Pongprayoon et al, 1991a). In vitro assay detected 2-hydroxy-4,4,7-trimethyl-1(4H)-naphthalenone, mullein, eugenol and 4-vinylguaiacol isolated from I. pes caprae that had inhibitory effect on the synthesis of prostaglandin (Pongprayoon et al, 1991b).…”
Section: Discussionmentioning
confidence: 97%
“…Eugenol is a well-known inhibitor of prostaglandin synthesis and also possesses antiinflammatory activity. Eugenol and guaiacol are also reported to inhibit leukocyte chemotaxis and prevent the production of oxygen free-radicals by leukocytes (Pongprayoon et al, 1991a). Others chemical studies related that I. pes-caprae contains phenolic and terpenoid substances that must to assure the antioxidative activity (Pongprayoon et al, 1991b).…”
Section: Discussionmentioning
confidence: 99%